ECO-INNOVATIONS FOR A SUSTAINABLE TOMORROW: A STUDY ON KIM STANLEY ROBINSON’S SIXTY DAYS AND COUNTING - Abima M; M. Saji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Green initiatives prioritize the healthy atmosphere of the planet and lead to a sustainable future. Inventions, nowadays, find their next phase with a concern for green environmental ideas. The green initiatives ideology includes renewable energy projects, using organic, eco-friendly products, energy-saving equipment, and many more. A harmonious life with nature is possible with eco-friendly approaches. This article focuses on the green harmonious initiatives in Kim Stanley Robinson’s science fiction Sixty Days and Counting. It also attempts to show the possible ways to use trees as carbon sinks, use clean, pollution-free energy, and all the possible ways that help in using eco-friendly alternatives to induce a harmonious life with nature. It also points out that the technologically dependent and economically successful country is not a successful country until it gets connected to green initiatives. Also, this paper examines the ideas that have to be in practice to achieve clean air, water, and land which is the need of the hour to promote harmony with nature.